Toxoplasma encephalitis in AIDS patients in São Paulo during 1988 and 1991. A comparative retrospective analysis - PASSOS, Luciana Neves; ARAÚJO FILHO, Orlando Florentino de; ANDRADE JUNIOR, Heitor Franco de (Revista do Instituto de Medicina Tropical de São Paulo, 2000)
We conducted a retrospective analysis of Toxoplasma encephalitis patients from Instituto de Infectologia Emílio Ribas, the main AIDS hospital of São Paulo, Brazil, during two different stages of the HIV epidemics, in 1988 (38 patients) and 1991 (33 patients). There were AIDS-related demographic differences, but the clinical presentation and diagnostic efficiency were similar, usually based on tomography and clinical response to therapy, with a clear distinction from other CNS infections, based on clinical and laboratory findings. Specific serologic studies were performed less often in 1991, with a high frequency of therapy change. The direct acute death rate from Toxoplasma encephalitis was high during both periods, i.e. 8/38 in 1988 and 10/33 in 1991. The direct acute death rate for the patients from the two periods as a whole was 25.4% (18/71), related to the time of HIV infection, absence of fever and presence of meningeal irritation at presentation, blood leukocytes higher than 10,000/mm³ and blood lymphocytes lower than 350/mm³. Toxoplasma encephalitis is a preventable disease when adequate prophylactic therapy is used and is relatively easy to treat in diagnosed HIV patients. Unfortunately, this severe and deadly disorder is the HIV diagnostic disease in several patients, and our data support the need for careful management of these patients, especially in those countries with a high toxoplasmosis prevalence where AIDS is concurrent with economic and public health problems.